Indirect GHG emissions in hydropower plants: a review focused on the uncertainty factors in LCA studies - Geller, Marla Teresinha Barbosa; Bailão, Jacqueline Lopes; Tostes, Maria Emília de Lima; Meneses, Anderson Alvarenga de Moura (Desenvolvimento e Meio Ambiente, 2020)
Although Life Cycle Assessment (LCA) is standardized, there is a wide range of approaches and discussions of the methodology evaluating of environmental impacts in different contexts in energy production. This review aims to present some findings, and highlight and discuss factors that influence the Life cycle Assessments (LCAs) of Hydropower Plants (HPPs) such as: indirect emissions; different stages of HPPs (construction, operation and decommissioning), the scale/productivity of HPPs; types of projects (reservoir and run-of-river), and land use. This study presents the comparison of different energy sources through the LCA and the comparison between several HPP with their different characteristics. Most of the results obtained by HPP LCAs indicate that the construction phase is the most influential phase for indirect emissions due to the use of steel and concrete. There is an important relationship between impact and production, since plants with higher productivity will have their impacts diluted during their lifetime. The comparison of the LCA results of HPPs with the LCA of other energy sources indicates that, for the category analyzed (Global Warming Potential- GWP), HPPs have a good environmental performance considering the emissions quantified. The object of this study is indirect emissions and not direct emissions, which are important, but require another approach. This review also indicates some uncertainties related to the LCA of the HPPs and the need to conduct future studies on the environmental impacts of UHEs. We also present suggestions that should contribute to improve the use of the LCA methodology.